2011
DOI: 10.3109/08039488.2011.596947
|View full text |Cite
|
Sign up to set email alerts
|

Swedish attitudes towards persons with mental illness

Abstract: The New CAMI-S came out as a useful tool to screen Swedish attitudes towards persons with mental illness. Most Swedes were prepared to live next to the mentally ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
2
26
0
2
Order By: Relevance
“…In our sample, women demonstrated less stigmatizing attitudes than men, which is consistent with the findings of studies from West European countries [38][39][40][41][42]. Additionally, individuals aged between 16 and 34 years had less favourable attitudes than their older fellow citizens.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our sample, women demonstrated less stigmatizing attitudes than men, which is consistent with the findings of studies from West European countries [38][39][40][41][42]. Additionally, individuals aged between 16 and 34 years had less favourable attitudes than their older fellow citizens.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, individuals aged between 16 and 34 years had less favourable attitudes than their older fellow citizens. Similar results were found by Högberg et al [39], who found people between 31 and 50 years to be less stigmatizing. In other studies, however, stigmatizing attitudes were found to be increasing with age [41,43] or having no significant influence [8,38,40].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A Japanese study [40] used different items but found one factor, fear of the mentally ill, resembling one of the factors of Brockington. A recent Swedish study [41] added behavioral items like the present study and revealed a related pattern, that is, four factors, intention to interact, fearful and avoidant, open-minded and prointegration, and community mental health ideology. Together, the referred studies, as well as the present study, have given strong indications of common attitude factors across different cultures.…”
Section: Discussionmentioning
confidence: 69%
“…Stigmatizing attitudes toward people with mental illnesses are prevalent and widespread . However, research has shown that women are less likely than men to endorse personal responsibility for the illness, and less likely to desire social distance from individuals with mental illnesses . Findings in relation to age differences in stigmatizing beliefs about mental illness are conflicting.…”
Section: Introductionmentioning
confidence: 99%